Functional Group Identification and Toxicity of Piper crocatum Red Betel Acetone Extract against Artemia salina by Brine Shrimp Lethality Test Method - Septaria Yolan Kalalinggi; Nunuk Hariani Soekamto; Firdaus (Universitas Islam Indonesia, 2023)
Identification of compounds and acetone extract activity from P. crocatum red shrimp has been done using phytochemical testing and Brine Shrimp Lethality Test (BSLT). The extraction begins with maseration using an acetone solvent and then the solvent is moved using an evaporator. Identification of extract function groups using the IR and GC-MS spectrum, as well as the toxicity test of the extract was carried out against the 48-hour Artemia salina Leach shrimp larva. The identification results showed the presence of flavonoids, phenylpropanoids, and steroids supported by GC-MS data and IR spectrum that indicated the existence of OH groups, C=O esters, C=O ketones, C=C olephins, C=C aromatic, C-O ester, and aliphatic CH. The results of probit analysis (LC50) showed that the acetone extract was highly toxicÂ (LC50 0-100 Î¼g/mL) to Artemia salina Leach with LC50 value of 2.4520 ppm.